Nutritional state of patients with neoplasia of head and neck in oncologicall treatment in a public hospital in west catarinian (Research, Society and Development, 2021)
Objective: To analyze the nutritional status of patient´s with head and neck cancer clinical and surgical cancer treatment at a public oncology referral hospital in western Santa Catarina. Methodology: Cross-sectional, exploratory and descriptive study with a quantitative approach, developed in a public hospital in western Santa Catarina with 35 patients diagnosed with malignant neoplasm of the head and neck  undergoing oncological treatment at the site. Data collection was carried out between March and August 2020. Results: Most of them were male (88.6%), with na average age of 59.5 years old, had incomplete elementary school, married and with son. The prevalence of diagnosis was oropharyngeal squamous cell carcinoma. Regarding ASG-PPP, the supremacy of the patients showed that the food intake in the last month is lower than normal and they present one or more symptoms that prevent them from eating enough in the last two weeks. Most of them still presented some degree of malnutrition, and need nutritional assessment and intervention in some degree of complexity. Anthropometry, however, points to eutrophic (48.8%) according to BMI, and the other measures indicate deficit or risk of deficit of tissues consistent with that found in the ASG-PPP. The most frequent factors that interfere with food were dry mouth and changes in taste. Conclusion: It is concluded that patients with head and neck cancer need some degree of intervention and/or nutritional guidance, based on the numerous symptoms they present, prevalence of malnutrition, as well changes in food consumption.